Penatalaksanaan Fisioterapi pada Kasus Cervical Root Syndrome dengan Modalitas Neuromuscular Tapping dan Hold Relax - Siti Sopur; Indah Permata Sari; Adi Saputra Junaidi (3031-8572, 2022)
Cervical root syndrome is a condition caused by irritation or compression of the cervical nerve roots by protrusion of the intervertebral disc. The cause of cervical root syndrome is21% due to trauma and overuse, while 70% of patients are due to processes such as spondylosis, hernia nucleus pulposus in the cervical area. objective: To determine the management of physiotherapy in cases of cervical root syndrome with neuromuscular tapping and hold relax modalities. Result: After four times therapy on these patients using the neuromuscular tapping and hold relax modality, the results showed a reduction in pain and increased range of motion conclusion: neuro muscular tapping and hold relax modalities can reduce pain and increase yourown range of motion.